Statins in Non-alcoholic Steatohepatitis - Torres-Peña, Jose D.; Martín-Piedra, Laura; Fuentes-Jiménez, Francisco (Frontiers in Cardiovascular Medicine, 2021)
Non-alcoholic fatty liver disease (NAFLD) is the primary cause of chronic liver disease. The range is extensive, including hepatocellular carcinoma, cirrhosis, fibrosis, fatty liver, and non-alcoholic steatohepatitis (NASH). NASH is a condition related to obesity, overweight, metabolic syndrome, diabetes, and dyslipidemia. It is a dynamic condition that can regress to isolated steatosis or progress to fibrosis and cirrhosis. Statins exert anti-inflammatory, proapoptotic, and antifibrotic effects. It has been proposed that these drugs could have a relevant role in NASH. In this review, we provide an overview of current evidence, from mechanisms of statins involved in the modulation of NASH to human trials about the use of statins to treat or attenuate NASH.